Conservation of the biologically active portions of staphylococcal enterotoxins C1 and C2. - Bohach, G A (1989)
We determined the primary sequence of staphylococcal enterotoxin (SE) C2 by sequencing its cloned structural gene, entC2. The entC2 structural gene contains an 801-base-pair open reading frame which encodes a 266-amino-acid precursor with a molecular weight of 30,608. Mature SE C2, produced by removal of the signal peptide, contains 239 amino acids with a molecular weight of 27,531. A sequence comparison between SE C2 and SE C1 showed that the 167 carboxyl amino acids in both toxins were 100% conserved. In contrast, the 72 N-terminal residues were 10% divergent. This provides additional evidence that carboxyl regions of staphylococcal and streptococcal pyrogenic toxins determine shared biological activities and cross-reactive epitopes.